Studies on the Mechanism of the Volatile Oils from Caoguo-4 Decoction in Regulating Spleen Deficiency Diarrhea by Adjusting Intestinal Microbiota. (27th January 2022) - Mei, Li; Wang, Fang; Yang, Ming; Liu, Zhiyong; Wang, Liangfeng; Chen, Qingyao; Li, Fengqin; Zhang, Xiaofei
Abstract : Background . The Caoguo-4 decoction, a classical Mongolian medicine formula, is widely used to treat spleen deficiency diarrhea (SDD) in Mongolian for decades. Previously, the Caoguo-4 decoction volatile oil has been confirmed to be effective in ameliorating symptoms of spleen deficiency diarrhea in an animal model. However, the underlying mechanism of the Caoguo-4 decoction volatile oil is yet to be established. The aim of the current study was to investigate the antidiarrheal effects and mechanism of the Caoguo-4 decoction volatile oil. Method . Wistar rats were randomly divided into 5 groups of 10 animals including control, model, positive, Caoguo-4 decoction, and Caoguo-4 decoction volatile oil groups (10 rats in each group). All the rats, besides those in the control group, were induced to develop SDD by a bitter-cold purgation method with Xiaochengqi decoction. The antidiarrheal effect of Caoguo-4 decoction volatile oil was evaluated by pathological section, serum D-xylose and AMS content, plasma MTL content, and gut microbiota analysis via 16S rRNA sequencing. Results . The results showed that the developed SDD rat model (model group) had decreased food intake, increased weight loss, soft stool, and bad hair color. When compared with the control group, serum was significantly reduced serum D-xylose and AML but increased MTL levels in the model group (p < 0.05 ). However, after treatment with either the Caoguo-4 decoction (the decoction group) or Smecta (the positive group) or volatile oil from the Caoguo-4 decoction (the volatile oil group), a significant increase in the serum D-xylose levels was observed. Additionally, AML levels significantly increased in the positive and volatile oil groups, and MTL levels significantly decreased in the decoction and volatile oil groups, when compared with the model group (p < 0.05 ). The pathological changes of the intestinal mucosa showed that the structure of the epithelium in the villi of the small intestine was affected, deformed, and incomplete in the model group when compared with the control group. However, either the decoction group or the volatile oil group recovered the villous morphology. The results of OTU analysis and alpha diversity analysis of intestinal bacteria showed that the intestinal microbiota of the SDD model rats showed an obvious decrease in richness and diversity of intestinal microbiota. But the intervention treatment of decoction and volatile oil could significantly recover the richness and diversity of intestinal microbiota. Conclusion . The intestinal microbiota destroyed in SDD modelling could be significantly improved by the Caoguo-4 decoction volatile oils, which provides reference for clinical medication.